2009
DOI: 10.1037/a0012958
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for prevention or promotion following social exclusion: Being rejected versus being ignored.

Abstract: Social exclusion evokes powerful motivations and emotions. The present studies examined how these motivations and emotions might differ following exclusion that is explicit, active, and direct (i.e., when one is rejected) versus implicit, passive, and indirect (i.e., when one is ignored). It was hypothesized that being rejected should produce a sense of social loss and lead to more prevention-focused responses, including withdrawal from social contact, thoughts about actions one should not have taken, and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
196
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(224 citation statements)
references
References 77 publications
(156 reference statements)
6
196
1
4
Order By: Relevance
“…So far we know very little about how cultures shape how individuals in different cultural groups engage in ostracism (also see Freedman, Williams, & Beer, 2016), which ostracism strategies individuals find most effective and painful (see Kerr & Levine, 2008), how they react when other individuals are ostracized (see Over & Uskul, 2016), and how individuals react to different types of ostracism (e.g., ignoring someone versus actively excluding them, see Molden et al, 2009). Thus, examining ostracism across different cultural groups focusing on different aspects of the ostracism experience from the target, the source and witness perspective will provide a more comprehensive understanding into the culture-ostracism link.…”
Section: General Discussion and Future Directionsmentioning
confidence: 99%
“…So far we know very little about how cultures shape how individuals in different cultural groups engage in ostracism (also see Freedman, Williams, & Beer, 2016), which ostracism strategies individuals find most effective and painful (see Kerr & Levine, 2008), how they react when other individuals are ostracized (see Over & Uskul, 2016), and how individuals react to different types of ostracism (e.g., ignoring someone versus actively excluding them, see Molden et al, 2009). Thus, examining ostracism across different cultural groups focusing on different aspects of the ostracism experience from the target, the source and witness perspective will provide a more comprehensive understanding into the culture-ostracism link.…”
Section: General Discussion and Future Directionsmentioning
confidence: 99%
“…Research on ostracism has shown that threats to people belonging evoke a variety of emotional and motivational responses. One of these responses is an enhanced state of vigilance during which there is a stronger concern for preventing further losses of social connection (Molden, Lucas, Gardner, Dean, & Knowles, 2009). Possibly as a result of having just played the ostracism game, Study 2 participants became more wary and were specifically impacted by the uncertain period during which a ball was tossed.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined whether the type of rejection affects the impact of rejection [Gerber and Wheeler, 2009; Note: Factors in parentheses represent those of interest to the present research. 504 Sinclair et al Molden et al, 2009;Romero-Canyas et al, 2010b]. Yet within the stalking literature, victims are advised that they should not let pursuers ''down easy'' by providing indirect, passive, rejections, but rather to explicitly reject stalkers [e.g., Carll, 1999;Cupach and Spitzberg, 2004;de Becker, 1997].…”
Section: Instigating Factor: Rejectionmentioning
confidence: 98%
“…Direct rejection has previously been defined as one that clearly communicates to individuals that they were rejected because they were not liked [Molden et al, 2009]. Paralleling our operationalization of an external rejection, we defined a direct rejection as one that uses an internal attribution, such that the rejection is attributed to the characteristics of the person being rejected.…”
Section: Weakmentioning
confidence: 98%